Iodine-stabilized He-Ne laser pumped by transverse rf-discharge - Boyko, O.V.; Negriyko, A.M.; Yatsenko, L.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
The results of experimental investigations of He-Ne/¹²⁷I₂ lasers (l = 633 nm) pumped by transverse rf-discharge are presented. Due to the low level of amplitude fluctuations, the frequency stability of such lasers reaches 5*10⁻¹³ for the integration time 100 s, and it is about six times as large as the stability of the lasers pumped by dc-discharge. The modulation shifts of the frequency of stabilized He-Ne/¹²⁷I₂ lasers were measured with high accuracy in the wide range of the frequency deviation 1.5 MHz ≤ D ≤ 20 MHz. The sources of the asymmetry of saturated-absorption resonances were determined as the joint action of the lenslike properties of the absorption medium and the elastic velocity-changing collisions of absorbing molecules. The results of a bilateral laser frequency comparison of the developed laser and the laser DE-3 (KIM, Kharkiv) are reported.